Are acute type A aortic dissections atherosclerotic? - Grewal, Nimrat; Dolmaci, Onur; Jansen, Evert; Klautz, Robert; Driessen, Antoine; Lindeman, Jan; Poelmann, Robert E. (Frontiers in Cardiovascular Medicine, 2023)
Background: Type A aortic dissections (TAAD) are devastating aortic complications. Patients with Marfan syndrome, a bicuspid aortic valve or a thoracic aortic aneurysm have an increased risk to develop a TAAD. These predisposing conditions are characterized by a histologically thin intimal layer and hardly any atherosclerosis. Little is known about the susceptibility for atherosclerosis in patients with a type A aortic dissection. Objective: We aim to systematically describe atherosclerotic lesions in TAAD patients. Material and methods: A total of 51 patients with a TAAD (mean age 62.5 ± 10.8 years, 49% females) and 17 control patients (mean age 63 ± 5.5 years, 53% females) were included in this study. Cardiovascular risk factors were assessed clinically. All sections were stained with Movat pentachrome and hematoxylin eosin. Plaque morphology was classified according to the modified AHA classification scheme proposed by Virmani et al. Results: In the TAAD group thirty-seven percent were overweight (BMI > 25). Diabetes and peripheral arterial disease were not present in any of the patients. Fifty-nine percent of the patients had a history of hypertension. The intima in TAAD patients was significantly thinner as compared to the control group (mean thickness 143 ± 126.5 μm versus 193 ± 132 μm, p<0.023). Seven TAAD patients had a normal intima without any form of adaptive or pathological thickening. Twenty-three TAAD patients demonstrated adaptive intimal thickening. Fourteen had an intimal xanthoma, also known as fatty streaks. A minority of 7 TAAD patients had progressive atherosclerotic lesions, 4 of which demonstrated pathological intimal thickening, 3 patients showed early fibroatheroma, late fibroatheroma and thin cap fibroatheroma. In the control group the majority of the patients exhibited progressive atherosclerotic lesions: three pathologic intimal thickening, two early fibroatheroma, six late fibroatheroma, one healed rupture and two fibrotic calcified plaque. Discussion: This study shows that TAAD patients hardly exhibit any form of progressive atherosclerosis. The majority of TAAD patients showcase non-progressive intimal lesions, whereas the control group mostly demonstrated progressive intimal atherosclerotic lesions. Findings are independent of age, sex or the presence of (a history of) hypertension.